Status and potential of herbal applications in aquaculture: a review - Ahmad, Syahidah; Saad, Che Roos; Mohd Daud, Hassan; Abdelhadi, Yasser Mohammed (Iranian Fisheries Research Organization, 2015)
Disease are recognized as one of the major constraint to sustainable animal production which can cause significant economic loss especially in aquaculture. Various chemotherapeutic agents have been traditionally used in the treatment and prevention of diseases in farmed fish but they are not recommended since improper and continuous use of antibiotics may lead to potential development of antibiotic resistant bacteria, environmental pollution and accumulation of toxic residues in fish. Therefore, scientists have intensified efforts to exploit natural products such as herbs in developing alternative dietary supplements that enhance growth performance, and health and immune system of cultured fish, as these products are inexpensive, safer, effective, and can be easily prepared and are biodegradable. This review discusses the findings from different studies related to the in-vitro and in-vivo applications of herbs and plant extracts or their combinations, in relation to appetite stimulator, growth promoter, antimicrobial, antiparasitic, antioxidant and immunostimulation in fish.